PENGARUH CITRA DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN (STUDI PADA PELANGGAN GO-JEK DI SEMARANG) - Ditto Putra Aryanansa, 12.05.51.0076; Setiawan, Mulyo Budi (Students Journal of Economic and Management, 2018)
This study attempts to analyze influence imagery and the quality of care of customer loyalty with satisfaction customers as variable intervening a study of Go-Jek Semarang.The population in this study is the customer Go-JekSemarang.The sample was conducted by using the method purposive sampling. With the results of the spread of the questionnaire obtained sample which used sample obtained a hundred people .The results of the study showed that (1) Noted for his imagery significant impact on customer satisfaction , (2) The quality of services has no significant impact on customer satisfaction , (3) Noted for his imagery of its effect on customer loyalty , (4) The quality of services has no significant impact on customer loyalty , (5) Significant impact on the customer satisfaction in customer loyaltyKeywords: Image, quality of services customer satisfaction, and customer loyalty